2021
DOI: 10.3390/cells10102602
|View full text |Cite
|
Sign up to set email alerts
|

Adipose Tissue Steroid Receptor RNA Activator 1 (SRA1) Expression Is Associated with Obesity, Insulin Resistance, and Inflammation

Abstract: Steroid receptor RNA activator 1 (SRA1) is involved in pathophysiological responses of adipose tissue (AT) in obesity. In vitro and animal studies have elucidated its role in meta-inflammation. Since SRA1 AT expression in obesity/type 2 diabetes (T2D) and the relationship with immune-metabolic signatures remains unclear, we assessed AT SRA1 expression and its association with immune–metabolic markers in individuals with obesity/T2D. For this, 55 non-diabetic and 53 T2D individuals classified as normal weight (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…TNFα also predicted SRA1 adipose expression in both normal weight and obese populations, regardless of diabetes status. Taken together, this study revealed specific association patterns of the adipose SRA1 expression with diverse immune markers, most of them being inflammatory by nature [ 42 ].…”
Section: Introductionmentioning
confidence: 90%
See 3 more Smart Citations
“…TNFα also predicted SRA1 adipose expression in both normal weight and obese populations, regardless of diabetes status. Taken together, this study revealed specific association patterns of the adipose SRA1 expression with diverse immune markers, most of them being inflammatory by nature [ 42 ].…”
Section: Introductionmentioning
confidence: 90%
“…HbA1c levels of <5.7, 5.7–6.4%, and >6.4% represented normal, prediabetes, and diabetes status, respectively. Height, weight, waist and hip circumferences, BMI, and PBF were measured and calculated as previously described [ 42 ]. For the assessment of insulin resistance (HOMA-IR) and insulin sensitivity, fasting blood glucose and insulin levels were used to determine HOMA index [ 43 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…For each real-time PCR reaction, 50 ng of cDNA template was amplified using Inventoried TaqMan Gene Expression Assay products (mouse IL-6: Hs00446190_m1; 1) Pparg: Mm00440940_m1;Fabp4: Mm00445878_m1; mouse GAPDH:Mm99999915_g; human IL-6: Hs00985639_m1; Ppar g: Hs01115513_m1; PLIN2: Hs00605340_m1; 1; human GAPDH: 4310884E using two gene-specific primers, one TaqMan MGB probe (6-FAM dye-labeled), a TaqMan ® Gene Expression Master Mix (Applied Biosystems, Foster City, CA, USA), and a 7500 Fast Real-Time PCR System (Applied Biosystems, Foster City, CA, USA) [28][29][30][31]. The target mRNA levels were normalized against GAPDH mRNA relative to the control, and calculated using the 2 −∆∆CT method [32]. Relative mRNA expression was expressed as fold expression relative to the average of control gene expression.…”
Section: Real-time Rt-pcrmentioning
confidence: 99%